Comparative behaviour of sympatric moulting populations of Common Eider Somateria mollissima and King Eider S. spectabilis in central West Greenland - Frimer, Ole (Wildfowl, 1995)
Activity budgets and distribution patterns of Common Eider moulting at Disko Island, West Greenland, were studied and compared to the behaviour of King Eider moulting in the same general area (Frimer 1994b). Both species are diurnal feeders who spend most of the night resting. The daily foraging pattern was essentially similar in the two species, with peak intensity early and late in the day, and there was no significant difference in the amount of time spent foraging. However, while Common Eiders foraged near the rocky shoreline at depths of less than 15 m, King Eiders foraged mainly on silt bottom at depths of 15-25 m. Dabbling comprised between 10.7% and 45.6% of the foraging time in Common Eiders, and less than 1% in King Eiders. The total food niche overlap between the two eider species is estimated to be less than 16%. A low interspecific competition may be crucial to the survival of the species in the late autumn and winter, when days are short and the birds spend most of the day foraging. Some adaptations of the species to their feeding habitats are discussed.